Efficacy and safety and analysis of thrombopoietin receptor agonists for the treatment of immune thrombocytopenia in adults: analysis of a systematic review and network meta-analysis of randomized controlled trials and results of real-world safety data - Liu, Yumeng; Zhang, Ni; Jiang, Tingting; Li, Yanping; Xiong, Yu; Liu, Yao (Frontiers in Medicine, 2025)
This study aimed to compare the efficacy and safety of thrombopoietin receptor agonists (TPO-RA) in the treatment of immune thrombocytopenia (ITP) in adults. A systematic review was conducted using network meta-analysis and a disproportionality analysis based on the FDA Adverse Event Reporting System (FAERS) database to evaluate hemorrhagic and thrombotic events of clinical concern. Our network meta-analysis included 14 randomized controlled trials (RCTs) involving 1,454 patients. The results indicated that, in terms of efficacy, romiplostim [odds ratio (OR), 0.04; 95% confidence interval (CI), 0 to 0.68] was the most effective, followed by avatrombopag, hetrombopag, and eltrombopag. Regarding safety, there were no significant differences in the safety profiles of the four TPO-RA compared to placebo. According to the surface under the cumulative ranking curve (SUCRA), avatrombopag exhibited the highest safety ranking at 23.8%. Within the FAERS database, we identified 982 cases of TPO-RA-related hemorrhagic and thrombotic events. The highest number of preferred terms (PTs) associated with romiplostim was 26, followed by 18 for eltrombopag and 7 for avatrombopag. The findings of this study suggest that romiplostim exhibits significant efficacy, whereas avatrombopag presents a superior safety profile. In the context of clinical second-line treatment, the selection of the most suitable TPO-RA should be guided by the specific circumstances of each patient.Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails